2019
DOI: 10.21046/2070-7401-2019-16-5-356-363
|View full text |Cite
|
Sign up to set email alerts
|

Forest fires in Russia: specifics of the 2019 fire season

Abstract: По предварительным оценкам, полученным на конец октября 2019 г., площадь территорий, которые были пройдены пожарами в сезоне этого года, близка к 10 млн га. В работе отмечается, что до настоящего времени с начала регулярных однородных спутниковых наблюдений за лесными пожарами, которые фактически ведутся с 2000 г., ситуация, когда площади, покрытые лесом и пройденные лесными пожарами, приближались или превосходили 10 млн га, происходила только три раза (в 2003, 2012 и 2018 гг.). Обращается внимание, что в 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Climatic change stimulates the increase in forest losses by raising the frequency of pest outbreaks [33,34] and forest fires. The biggest forested Russian regions, such as Yakutia and Krasnoyarsk Krai, have suffered significant fires in their northern parts [35][36][37].…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…Climatic change stimulates the increase in forest losses by raising the frequency of pest outbreaks [33,34] and forest fires. The biggest forested Russian regions, such as Yakutia and Krasnoyarsk Krai, have suffered significant fires in their northern parts [35][36][37].…”
Section: Dataset Descriptionmentioning
confidence: 99%
“…The problem of uncontrolled wildfires that threaten even Strict PAs does not seem a concern of local authorities because most of them burn remote areas where authorities are not obliged to take action [11]. Nonetheless, Russian prosecutors confirmed that some of the enormous wildfires that burned Siberian forests in the last years were started deliberately by arsonists trying to conceal illegal logging activity [12].…”
Section: Resultsmentioning
confidence: 99%
“…However, a significant portion of these forests are in the northern hard-to-reach areas. They are unsuitable for logging, but in recent years have been intensively affected by forest fires [33,34].…”
Section: Imperfect Competition and Spatial Heterogeneity In The Russi...mentioning
confidence: 99%